State of Index-Based Crop Insurance Interventions for Smallholder Farmers and Agribusinesses in East Africa - Osumba, Joab; Recha, John W.M.; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This review of index-based agricultural insurance for the Climate Resilient Agribusiness for Tomorrow—CRAFT (https://crafteastafrica.org/) project was part of a wider effort to strengthen understanding in the enabling environment for scaling in CRAFT interventions. The findings can be used to design an appropriate agricultural insurance intervention in future. Climate-smart crop insurance is one of the interventions that was proposed in the project. Smallholder farmers and agribusinesses (SMEs and cooperatives) often lack access to financial services such as insurance, which could help them to prepare, invest, safeguard, and adapt. Opportunities for tailored index-based insurances to cover climate-related crop losses are still underdeveloped in eastern Africa. Further, there is a possibility of the risk or likelihood or prospect of climate change to raise insurance prices. Hence the urgent need to help climate-proof the CRAFT project value chains through financial services such as insurance. In the wider CRAFT enabling environment, there were opportunities for access to insurance services that were either not yet developed (such as tailored index-based insurances to cover for climate-related crop losses) or did not experience sufficient incentives due to high risks and uncertainties, including those related to climate change. East African governments need support in facilitating access to these financial services for agribusinesses and entrepreneurial farmers.